2014
DOI: 10.1002/tox.22065
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic exposure to diflubenzuron causes health disorders in neotropical freshwater fish, Prochilodus lineatus

Abstract: The action of diflubenzuron (DFB) was evaluated in a freshwater fish, Prochilodus lineatus, after exposure to 0.06, 0.12, 0.25, or 0.50 mg L(-1) DFB for 14 days. Erythrocyte nuclear abnormalities (ENA), the gill activity of Na(+)/K(+)-ATPase, H(+)-ATPase and carbonic anhydrase (CA), and lipid peroxidation (LPO) and histopathological changes in the gills and liver were determined. The number of micronuclei increased in fish exposed to 0.25 and 0.50 mg L(-1) DFB. Plasma Cl(-) and the CA activity decreased, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 42 publications
1
8
0
2
Order By: Relevance
“…In this work, the action of Thiodan ® at sublethal concentrations was found not to affect the liver as a whole, but did manifest itself in the form of the occurrence of specific lesions in the liver parenchyma in the different treatments. DTC in the livers of lambaris were not severe, as they showed no necrosis and exhibited only Stage I and II morphological changes (these stages being classified as repairable) as reported in other studies (Langiano Vdo and Martinez, ; Simonato et al, ; Benze et al, ; Wolf et al, ). Moreover, an increased frequency of histological alterations can indicate dysfunctions induced by toxic agents, since metabolically active areas of the liver are reduced, leading to a possible reduction in the overall functions performed by this organ (Oliveira Ribeiro et al, ; Pacheco and Santos, ; Benze et al, ).…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…In this work, the action of Thiodan ® at sublethal concentrations was found not to affect the liver as a whole, but did manifest itself in the form of the occurrence of specific lesions in the liver parenchyma in the different treatments. DTC in the livers of lambaris were not severe, as they showed no necrosis and exhibited only Stage I and II morphological changes (these stages being classified as repairable) as reported in other studies (Langiano Vdo and Martinez, ; Simonato et al, ; Benze et al, ; Wolf et al, ). Moreover, an increased frequency of histological alterations can indicate dysfunctions induced by toxic agents, since metabolically active areas of the liver are reduced, leading to a possible reduction in the overall functions performed by this organ (Oliveira Ribeiro et al, ; Pacheco and Santos, ; Benze et al, ).…”
Section: Discussionsupporting
confidence: 74%
“…This change would demonstrate a pathophysiological condition caused by lack of biliary excretion and metabolism (Pacheco and Santos, ) through the lack of release of the bile into the digestive tract (Simonato et al, ; Benze et al, ). This type of change can be found in fish exposed to toxins (Pacheco and Santos, ; Benze et al, ) and also in fish that have some nutritional problem when kept in captivity (Langiano Vdo and Martinez, ). The present study found that the different concentrations of Thiodan ® in the different 96‐hr treatments were insufficient to develop histopathological evidence of bile stagnation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations